2013
DOI: 10.1007/s00299-013-1395-4
|View full text |Cite
|
Sign up to set email alerts
|

Pollen transcriptome analysis of Solanum tuberosum (2n = 4x = 48), S. demissum (2n = 6x = 72), and their reciprocal F1 hybrids

Abstract: Pollen mRNAs were different in reciprocal F 1 hybrids, which were probably caused by a cytoplasm-nuclear chromosomal genes interaction. We have found reciprocal differences in crossability between F1 hybrids of Solanum tuberosum (T) and a Mexican wild potato species S. demissum (D). When the reciprocal hybrids were crossed as pollen parents with S. demissum, a significantly higher berry-setting rate was obtained in TD compared with DT. In this study, we performed a whole-genome transcript analysis of the polle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Other species for which mature pollen transcriptome data have been published include maize (Ma et al 2008 ; Davidson et al 2011 ; Chettoor et al 2014 ), soybean (Haerizadeh et al 2009 ), grapevine (Fasoli et al 2012 ), potato (Sanetomo and Hosaka 2013 ), woodland strawberry (Hollender et al 2014 ), and most recently lily (Lang et al 2015 ).…”
Section: Comparative Pollen Transcriptomicsmentioning
confidence: 99%
“…Other species for which mature pollen transcriptome data have been published include maize (Ma et al 2008 ; Davidson et al 2011 ; Chettoor et al 2014 ), soybean (Haerizadeh et al 2009 ), grapevine (Fasoli et al 2012 ), potato (Sanetomo and Hosaka 2013 ), woodland strawberry (Hollender et al 2014 ), and most recently lily (Lang et al 2015 ).…”
Section: Comparative Pollen Transcriptomicsmentioning
confidence: 99%
“…To understand trends in genetic diversity changes in Chilean cultivars, we applied a set of commonly used markers specific to different loci of mitochondrial DNA [ 30 , 34 , 62 ] and demonstrated that all living Chilean accessions with the W-type cpDNA possessed the α-type mtDNA and the D-type cytoplasm which is characteristic for wild Mexican polyploid species, including S. demissum [ 62 , 63 , 66 ]. In addition, we showed that all living accessions with the D-type cytoplasm exhibited R1 - or R3a -gene-specific markers.…”
Section: Discussionmentioning
confidence: 99%
“…Finding the new chlorotypes within subsets of contemporary living Chilean accessions that were not detected within Chilean landraces collected in 1928 (before the late blight epidemics in Chile) might indicate genetic erosion through the introduction/introgression of genetic material from commercial varieties having in their pedigree wild species of the secondary potato gene pool. Moreover, detection of the D-type cytoplasm in living Chilean accessions typical only for Mexican polyploids [ 62 , 63 , 66 ] indicates introgression from wild Mexican species S. demissum belonging to the secondary gene pool. It is important to note that potato varieties that were developed in the 20th century represent high genetic diversity resulting from the introduction of many introgressions of wild species both from the primary and secondary potato gene pools [ 67 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several dedicated investigations for different stages and cell types representing pollen are available (Bokvaj et al 2015;Chettoor et al 2014;Davidson et al 2011;Fasoli et al 2012;Haerizadeh et al 2009;Hafidh et al 2012;Hobo et al 2008;Hollender and Kang 2014;Lang et al 2015;Ma et al 2008;Sanetomo and Hosaka 2013;Suwabe et al 2008;Wei et al 2010). Indeed, gene expression studies by RNA-seq permitted to identify around 150 different pollen-expressed genes in different plant species associated with a range of different functions, including cell wall metabolism, cytoskeleton and signaling (Honys and Twell 2003;Palanivelu and Tsukamoto 2012;Rutley and Twell 2015).…”
Section: Next Generation Sequencing (Ngs) Datamentioning
confidence: 99%